Implementation of the Nested Integrated Learning Model in IPAS Material for 4th Grade - Chasanah, Maghfirotun; Wiyani, Novan Ardy (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
This study explores the Nested Integrated Learning Model as part of the Fogarty approach and its application in teaching Natural Sciences and Social Studies (IPAS) within the context of the independent curriculum. The primary focus is to analyse the impact of this model on students' comprehension, utilising the Classroom Action Research (CAR) method across multiple cycles. The research findings indicate that the nested integrated learning model positively influences students' understanding of IPAS subjects. The hierarchical and nested approach in delivering the content provides a more in-depth understanding. The study also highlights the crucial role of collaboration among teachers in effectively implementing this model. This research contributes to our understanding of the effectiveness of the Nested Integrated Learning Model, particularly in enhancing students' comprehension of interdisciplinary concepts. Practical implications include the potential adoption of this model within the independent curriculum at the elementary school level. By strengthening the empirical foundation, this research can serve as a guide for educational practitioners and policymakers in designing a curriculum that is holistic and relevant to student's development in the current educational landscape.